Peningkatan Keterampilan Kitabah Arabiyah Mahasiswa Melalui Metode Tutor Sebaya - Setiadi, Syamsi (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract: The learning of Arabic writing at Universitas Negeri Jakarta still faced some difficultiesin order to develop the students’ skill. The purpose of this study is to empirically examine the effectiveness of peer teaching method on the skills of students in Arabic writing. The method is classroom action research with the treatment as much as two cycles (rounds), each round consists of four stages, including: planning, implementation, observation and reflection.The subject of this research was 24 students of the Arabic Education Program at State University of Jakarta, in which each group consisted of 3-4 students. The results of classroom action research showed that learning with peer tutors are proven to improve student’s skills in Arabic writing of students.Peer tutoring learning method hasaccounted for 3.83 from the pretest to the first cycle, and 2.19 from the first cycle to the second cycle of improvement on students’ writing skill. This research proved that activelearning can be done without involving a lot of teachers. Besides, the learning process can be maximized with the existing potentials by, among others, through peer tutoring. Keywords:peer teaching method, action research, Arabic writing